2019
DOI: 10.1080/00016357.2019.1598573
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experiences of supervised jaw-neck exercise among patients with localized TMD pain or TMD pain associated with generalized pain

Abstract: Objective: To evaluate temporomandibular disorder (TMD) patients' experiences of a supervised jawneck exercise programme. Materials and methods: The study used a mixed method design. All patients were diagnosed with myalgia according to the Research Diagnostic Criteria for TMD and divided into local myalgia (n ¼ 50; 38 women, mean age 43 yrs, SD 14), and myalgia with generalized pain (n ¼ 28; 27 women, mean age 43 yrs, SD 13). Patients participated in a ten-session supervised exercise programme that included r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Stretching of the jaw muscles could lead to a reduction in the symptoms of TMD as well as an improvement in mandibular function (13). In addition, the neuromuscular, vascular, and rehabilitationary benefits of jaw exercise and posture correction exercise for TMD patients have been reported in previous studies (31,32). The positive effect of relieving pain and improving mandibular mobility may thus be assigned to the exercise therapy for patients with The use of occlusal splints for patients with TMD is common in dentistry (7,8).…”
Section: Discussionmentioning
confidence: 95%
“…Stretching of the jaw muscles could lead to a reduction in the symptoms of TMD as well as an improvement in mandibular function (13). In addition, the neuromuscular, vascular, and rehabilitationary benefits of jaw exercise and posture correction exercise for TMD patients have been reported in previous studies (31,32). The positive effect of relieving pain and improving mandibular mobility may thus be assigned to the exercise therapy for patients with The use of occlusal splints for patients with TMD is common in dentistry (7,8).…”
Section: Discussionmentioning
confidence: 95%
“…The biomechanical theory suggests a relationship between functional load and capacity of the masticatory system ( 8 ). Its long-lasting overuse and/or overload may induce pain and dysfunction in people with decreased resistance within the musculoskeletal system ( 9 , 10 ). Some authors emphasize that temporomandibular disorders are always related—directly or indirectly—to the myofascial component, i.e., trigger points (TrPs) of the head and neck ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, a study based on myofascial TMD patients reported that conventional treatment including oral appliances resulted in significant pain reduction in both groups of localized and widespread pain at 1‐year follow‐up (Doepel et al, 2018). Another study showed that TMD patients demonstrated a positive response to exercise therapy regardless of the presence of widespread pain (Storm Mienna et al, 2019). This was also true with our study groups as both groups experienced significant decreases in pain ratings although the amount was smaller in the widespread pain group.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic widespread pain has been associated with increased deterioration of general health condition (Sylwander et al, 2020), and facial pain with concomitant widespread pain is related to increased psychological disturbances such as depression (Sipilä et al, 2006). However, studies on treatment response in TMD patients with widespread pain are sparse and show conflicting results (Doepel et al, 2018; Raphael & Marbach, 2001; Storm Mienna et al, 2019). The current lack of scientific data to guide treatment planning is troublesome when considering the significant negative impact of widespread pain on long‐term overall health of TMD patients.…”
Section: Introductionmentioning
confidence: 99%